Impact of COVID-19 on outbound medical tourism: An empirical study - Khandakar, Shariful Khandakar; Tumpa; Nayeema (Journal of Tourism Management Research, 2023)
This study attempts to analyze the overall outbound medical tourism situation in Bangladesh, more specifically in the city of Dhaka, during the COVID-19 pandemic. The primary focus of the study is to identify the effect of COVID-19 on outbound medical tourism. To attain the objectives of the study, a quantitative research technique was used, and data were collected from respondents involved in outbound medical tourism through convenience sampling. The study’s samples were 100 people from Dhaka who were patients, medical attendants, relatives of patients, neighbors of patients, and closely related entities of outbound medical tourism. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results reveal that the COVID-19 situation had a significant impact on outbound medical tourism; the effects were measured through various factors, including accessibility, cost, the quality of domestic medical services, the information gap, and technological advancement. The results of the study provide insights to those involved in outbound medical tourism and offer guidelines to recover from this problem. Future research can consider the whole of Bangladesh and conduct a longitudinal study to increase the generalizability of the result.